Behavioural Consequences of the Performance Measurement System (PMS) in a Decision-Facilitating Role – A Review - Abdul Rasit, Zarinah; Ismail, Kamisah (Asian Journal of Accounting Perspectives, 2012)
The shortcomings of traditional PMS have led to the use of a more comprehensive PMS, which is widely used for decision-facilitating as well as decision-influencing purposes. Performance measurements for decision-facilitating or a cognitive role refer to the use of PMS to provide information to guide managers in decision-making whilst performance measurements used for a decision-influencing or motivation role refers to their use in the performance evaluation functions. Considerable prior PMS research identified the inconsistent findings in the relationship between PMS and organisational performance, thus, promoting the subsequent PMS related research to further explore the behavioural implications of PMS. This paper discusses the review of the literature examining the behavioural consequences of PMS. This review of the literature identified the conflicting findings from prior research and determined that research examining the informational characteristics of PMS on individual behaviour is still lacking.